Investigating the Role of Job Engagement and Job Self-Efficacy With Job-Family Conflict in Female Nurses of Tehran - Helia Rahimi; Abdolrahim Kasaee; Esmail Asadpour (Hamadan University of Medical Sciences, 2019)
Abstract Introduction: Many nurses face to challenge of balancing their job and family roles.The purpose of this study was to Investigating the Role of Job engagement and Job Self-efficacy in predicting job-family conflict in female nurses. Methods: In this study that was descriptive-correlational, the statistical population was all female nurses of Tehran state hospitals in the second three months of 2016 in 1200 people. Out of this, 381 subjects were selected by cluster sampling method, and were evaluated by family-job and self-efficacy  questionnaires. For statistical analysis of data the SPSS software(version 22) and the descriptive and inferential statistics methods such as Pearson correlation coefficient and multiple stepwise regression was used. Results: The results showed a significant negative correlation between the overall job engagement score and its components (P≤ 0.01,F=28/127). In addition, there is a negative significant correlation between components of job self-efficacy and overall score of self-efficacy with job-family conflict and family-job conflict(P≤ 0.05,F=126/93). Conclusion: Job engagement and job self-efficacy reduces job-family conflict that the obtained results from research can be used in nurses' curriculum designing to reduce job-family conflict. Keywords: Job engagement, Job self- efficacy , Job-family Conflict, Nurses